(untitled) - Williams, Brian K. (New York, NY, 2011)
Utilizing a practical, applied approach to technology, this text intends to foresee and define the impact of digital convergence, the fusion of computers and communications. It acknowledges the various priorities imposed by the Internet and World Wide Web
Keywords: Computers,Telecommunication systems,Information technology,Công nghệ thông tin,Tin học